(untitled) (Web of Teachers: Inderscience Research, 2024)
Modern educational methodology requires new approaches to develop students’ knowledge and skills in a changing world. This article presents an experimental test on the teaching of chemistry in the 27th school of Bukhara. The experiment was conducted among students of the 10th and 11th grades based on two groups - experimental and control groups. The experimental group received training based on new teaching methods, and the control group received training based on traditional methods. The results of this experiment showed that new teaching methods are more effective than traditional methods in increasing students’ knowledge level, motivation and interest in chemistry. The article emphasizes the importance of varied teaching methods in improving the quality of education and provides important directions for future educational strategies.